Kartika Handayani et.al ANALISIS TINGKAT KEPATUHAN DAN KEBERHASILAN TERAPI ANTIRETROVIRAL PADA PASIEN HIV/AIDS DI PUSKESMAS KOTA BANDAR LAMPUNG TAHUN 2022 - Kartika, Kartika Handayani; Arozal, Wawaimuli; Sumiati, Yati (JFL : Jurnal Farmasi Lampung, 2023)
HIV/AIDS is one of the hazardous infectious diseases that can cause death. To this day, combination antiretroviral treatment (ARV) is the best therapy for patients infected with Human Immunodeficiency Virus (HIV). To determine the success of antiretroviral treatment, monitoring of therapy can be done by doing viral load test. The study purposes were to determine the relationship between the level of compliance and the success of antiretroviral therapy in HIV/AIDS patients at the Bandar Lampung City Health Center in 2022. The method used in this study was a quantitative method using a non-experimental design with a cross-sectional method. The results of the study showed that compliance to taking medication based on the MMAS scale with 37 complied patients (56,1%), 29 patients (43,9%) did not comply, patients with good knowledge were 36 (54,5%), and patients who had less knowledge were 30 (45,5%). HIV/AIDS patients who received support from their families were 34 (51,5%), and quite a lot of patients who did not receive family support, they were 32 patients (48,5%). HIV/AIDS patients who had no side effects from the drugs they were taking were 9 patients (13,6%), and patients who had side effects from the drugs they were taking were 57 patients (86,4%). Patients with undetectable viral load were 18 patients (27.3%), patients with <40 copies/ml were 34 (51,5%), and patients with >40 copies/ml (21,2%) were 14. In addition, there is a relationship between knowledge related to disease, family support, and drug side effects with medication compliance in HIV AIDS patients at the Bandar Lampung Health Center in 2022. There is a relationship between knowledge about the disease, family support, drug side effects, and compliance. Then, there is a relationship between patients’ compliance and the success of ARV drug therapy in HIV/AIDS patients. Keywords: medication complication, ARV, HIV/AIDS, viral load